Waste Water Disinfection by Titanium Dioxide (Tio2) Solar Photocatalysis - Grandawaw, M.M. (Machakos University, 2018)
The task of achieving suitable wastewater disinfection without formation of dangerous disinfection by products by chemical disinfectants, as well as increasing need for a versatile wastewater disinfection and reuse systems demands for a new technologies for efficient disinfection and microbial control mechanism. Titanium dioxide (TIO2) a metal oxide semiconductor nanomaterial has proved as a powerful antibacterial, antiviral and antifungal properties through diverse mechanism of photo catalytic production of reactive hydroxyl and oxygen species on their surfaces in the presence of solar photons hvwhich inhibits enzyme activity and DNA synthesis ,damages the bacterial cell components and viruses in wastewater that contains these pathogenic agents. This paper reviews the antimicrobial mechanism and disinfection efficiency of Titanium dioxide (TIO20 nanoparticle, discusses their merits, limitations and applicability for wastewater disinfection, and highlights research needs by involving more people in order to exploit innovative TIO2 nanomaterial in wastewater disinfection
Keywords: Water